1994
DOI: 10.1159/000227321
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron Compared with Granisetron in the Prophylaxis of Cisplatin-lnduced Acute Emesis: A Multicentre Double-Blind, Randomised, Parallel-Group Study

Abstract: This is the first international, multi-centre, double-blind, randomised, parallel group study to directly compare the efficacy and safety profile of a single intravenous dose of ondansetron (8 or 32 mg) with granisetron (3 mg) in the control of cisplatin-induced acute emesis. A total of 496 patients were randomised to receive one of three anti-emetic treatments prior to cisplatin chemotherapy (≥50 mg/m2). Of these, 165 and 162 patients received 8 and 32 mg of ondansetron, respectively, and 169 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 2 publications
0
38
0
1
Order By: Relevance
“…5-HT 3 -receptor antagonists have become the agents of choice in preventing acute CINV following both moderately and highly emetogenic chemotherapy [11,51]. Complete response and total control rates seen with specific drugs range from 60%-80% for moderately emetogenic chemotherapy [4,[52][53][54], 40%-60% for cisplatin-containing therapy [4,33,55,56], and 25%-60% for high-dose cisplatin regimens [33,35,47,57,58].…”
Section: Optimizing Efficacymentioning
confidence: 99%
“…5-HT 3 -receptor antagonists have become the agents of choice in preventing acute CINV following both moderately and highly emetogenic chemotherapy [11,51]. Complete response and total control rates seen with specific drugs range from 60%-80% for moderately emetogenic chemotherapy [4,[52][53][54], 40%-60% for cisplatin-containing therapy [4,33,55,56], and 25%-60% for high-dose cisplatin regimens [33,35,47,57,58].…”
Section: Optimizing Efficacymentioning
confidence: 99%
“…Outside of the HSCT setting, numerous studies have concluded that these agents provide equivalent control of N/V induced by highly emetogenic chemotherapy when administered at equipotent doses. [2][3][4][5][6][7][8] Although three of these agents have been extensively studied in HSCT patients over the last 8 years, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] limited data directly comparing these agents is available. [21][22][23] Ondansetron, the first 5-HT 3 receptor antagonist approved in the United States, has been the most widely studied and is most effectively used in combination with corticosteroids for prevention of CINV; granisetron's effects are also enhanced with the use of corticosteroids.…”
mentioning
confidence: 99%
“…To our knowledge no previous report has shown age differences in delayed nausea or vomiting (Carmichael et al, 1994;du Bois et al, 1992;Gandara et al, 1993;Italian Group for Antiemetic Research, 1994;Kaizer et al, 1994;Lindley et al, 1989;Roila et al, 1991). Interestingly, in more recent studies, the evidence provided for an inverse relationship between age and emesis in the acute phase has not been consistent (de Wet et al, 1993;Heron et al, 1994;Italian Group for Antiemetic Research, 1993;Ruff et al, 1994). This may be related to the introduction of new anti-emetic regimens.…”
Section: Effects On Nauseamentioning
confidence: 91%